2017
DOI: 10.3390/molecules22040515
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from the Rhizomes of Smilax china L. and Their Anti-Inflammatory Activity

Abstract: A new triflavanoid, kandelin B-5 (1), was isolated from the rhizomes of Smilax china L., together with six known phenylpropanoid substituted flavan-3-ols (2–7), nine flavonoids (8–16), two stilbenoids (17, 18), and two other compounds (19, 20). The structure of compound 1 was determined on the basis of 1D, 2D NMR and HR-ESI-MS data, as well as chemical method. Compounds 2–5, 8–12, 15, 17, and 19 were evaluated for anti-inflammatory activity. Only compounds 10, 15 and 17 showed slightly IL-1β expression inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Phenolic compounds are usually found in date palms, and these compounds also act as antiinflammatory agents [20]. These compounds exert their anti-inflammatory effect by inhibiting leukocyte migration and reducing serum lysozyme, NO, PGE-2, and malondialdehyde levels [7].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds are usually found in date palms, and these compounds also act as antiinflammatory agents [20]. These compounds exert their anti-inflammatory effect by inhibiting leukocyte migration and reducing serum lysozyme, NO, PGE-2, and malondialdehyde levels [7].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these compounds have received considerable attention as being potentially beneficial to health owing to their potent antioxidant activity as well as their hepatoprotective, hypoglycemic, and antiviral activities [ 9 ]. Recently, researchers from China reported that phenolic compounds from the rhizomes of Smilax china have anti-inflammatory activity [ 10 ]. Phenolic compounds in higher plants can be roughly divided into non-flavonoid and flavonoid compounds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…LPS (the main component of the cell wall of Gram-negative bacteria) is a potent inducer of human T-lymphocyte proliferation as part of host pro-inflammatory response [ 46 ]. In addition, the anti-inflammatory properties of some phytochemicals present in HDHE have been reported [ 47 , 48 , 49 , 50 ]. The use of anti-inflammatory agents is of great importance in the treatment of microbial infection [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%